2012
DOI: 10.1007/s10008-012-1852-y
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the system polydispersity on voltammograms of nanoparticles electrooxidation

Abstract: The paper proposes a mathematical model describing electrooxidation of a polydisperse system of metal nanoparticles from the surface of an indifferent macroelectrode. It is shown that the degree of dispersion of a nanoparticle ensemble affects the shape of oxidation voltammograms. When the degree of dispersion rises and the average size of nanoparticles becomes smaller, the range of oxidation potentials increases. The results of the experimental study of electrooxidation of gold nanoparticles with different de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 9 publications
1
15
0
Order By: Relevance
“…Even if we admit that their shape is fuzzy, this shape must be "uniform" with similar characteristics in size and structure. Brainina et al studies [23][24][25][26][27][28] show very well the shifts of the peaks that are consistent with the positive values of the tension, τ. But the considered systems are usually too widely polydisperse for properly applying eq.…”
Section: Resultssupporting
confidence: 55%
“…Even if we admit that their shape is fuzzy, this shape must be "uniform" with similar characteristics in size and structure. Brainina et al studies [23][24][25][26][27][28] show very well the shifts of the peaks that are consistent with the positive values of the tension, τ. But the considered systems are usually too widely polydisperse for properly applying eq.…”
Section: Resultssupporting
confidence: 55%
“…These data are due to the formation of larger aggregates of silver. An analogical effect is found for gold nanoparticles in 21 . It is found that electrochemical activity of AgNPs does not depend on the order of addition of reagents during their obtainment (curves (-), (···), Fig.…”
Section: Resultsmentioning
confidence: 90%
“…SPE was rinsed thoroughly with distilled water. They were used as it is ΔG°Free Gibbs energy of nanoparticles c 4,592 J mol −1 a Diffusion coefficient is taken as intermediate magnitude between 1.028×10 −5 and 3.39×10 −5 cm 2 s −1 given in [19] and [20] b Standard ox/red potential is calculated for pH=3, using the magnitude E°=0.18 V given in [21] for pH=7 c ΔG°for nanoparticles size equal to 8 nm is calculated with the use of formula (14) from [23] Calculation parameters: k chem =4×10 9 , r NO2 =0 (a), k chem = 0, r NO2 =0 (b), k chem =0, r NO2 =149 pm (c). Other parameters are given in Table 1 Fig .…”
Section: Electrodes Preparationmentioning
confidence: 99%